The Production Effect Improves Memory in 7‐ to 10‐Year‐Old Children. Issue 3 (16th May 2019) - Pritchard, Verena E.; Heron‐Delaney, Michelle; Malone, Stephanie A.; MacLeod, Colin M.
Abstract : The production effect—whereby reading words aloud improves memory for those words relative to reading them silently—was investigated in two experiments with 7‐ to 10‐year‐old children residing in Brisbane, Australia. Experiment 1 ( n  =   41) involved familiar printed words, with words read aloud or silently appearing either in mixed‐ or blocked‐list formats in a within‐subject design. Recognition for words read aloud was better than for those read silently, an effect consistent across both list formats. These results were confirmed in Experiment 2 ( n  =   40) using longer lists of printed novel nonwords. Final analyses indicated that the production effect was comparable for words and nonwords. Findings are discussed in relation to the distinctiveness account and the use of production as a mnemonic in children.